O excepcional e a excepcionalidade da ordem sócio-cultural - Sant'Anna, Gilson Carlos (1988)
The education for 'handicapped' children is the object of this critical analysis, based upon the practice of Equipe Técnica de Educação Especial (ETESP), a branch of Secretaria Estadual de Educação do Estado do Rio de Janeiro, representative of the educacional system as the locus of power relationships. The theoretical background of this critical analysis questions the concept of normality in 'conformity with Canguilhem's thought and brings together Lacan and Marx's theories, specially that one of the determination and perrnanence of the social and cultural within which we live in. The institutional practices were defined accordingly to Foucault's point of view as the gradual process of production of docile and submissive bodies. The technicians and teachers of the ETESP work in this direction to guarantee and to perpetuate the hegemony of the dominant class, submitting the 'handicapped' children who don't accept the school rules to a normative practice. The necessity of changing the concept of 'handicapped' children and the possibility of creation of new spaces and methodologies are indicated as ways of transformation of the present picture of the education for 'handicapped' children.